Вы находитесь на странице: 1из 9

f (x) = Ln(x)

x = 1 2 x = 3

2

x =

1

2

x = 3

2

Long(f (x)) = b 1 + (f (x)) 2 dx = 3

a

1

2

2

1 +

x 2

1

dx

1 +

F(x) =

1 2 dx =

x

t

x

x dt =

t

2

t 1 dt =

t

2

1 + x 2 dx =

x

t 2 = x 2 + 1,

dx =

t

x dt

2t dt = 2x dx

t 2 1 + 1

t 2 1

dt =

t 2 1 + 1 dt =

1

=

1 2 t + 1 + t dt = 1 2 (Ln|t1|−Ln|t+1|)+t =

1

2

t 1

1

2 Ln

t

1

t

+ 1

+ t =

tArgT h(t) = 1 2 Ln x 2 + 1 1 + x 2 + 1 =

x 2 + 1 + 1

1 Ln ( x 2 + 1 1) 2

2

x

2

+

x 2 + 1 = Ln x 2 + 1 1 + x 2 + 1

x

Long(Ln(x)) = F 3

2

F

1

2

=

Ln 13 2 + 13

3

2

Ln( 5 2) + 5

2

1,503232006

= Ln 65 + 2 13 2 5 4 + 13 5

3

2

1 < x < 1

1 Ln 1 + x

1 x

2

ArgT hx =

=

1 Ln(x) dx + 3 Ln(x) dx =

1

2

1

2

1

F(x) = Ln(x)dx =

xLn(x) x

u = Ln(x), dv = dx,

= F 1 2 + F 3 2F (1) =

2

Ln 27

16

2

=

0,2616240718

1
2 Ln(x) dx + 3 Ln(x) dx

1

2

du = v = x

1

x dx

= xLn(x) x x dx =

1

1

2 Ln( 2 )

1

1

2 + 3 2

Ln( 3 ) 3 + 2 =

2

2

0 < x 1 < y 1 (x n ), (y n )

n 2

x n = x n1 · y n1 , y n = x n1 + y n1

2

a + b

> ab a+b > 2 ab (a+b) 2 > 4ab a 2 +b 2 2ab = (ab) 2 > 0

2

y n+1 y n = x n + y n

2

y n = x n y n < 0

2

x n x n+1 = x n x n y n = x n ( x n y n ) < 0

0 < x n < x n+1 < y n+1 < y n < y 1 x n y n y n λ , x n µ , µ λ

λ = λ + µ

⇒ λ = µ
2

y n x n 0

y n+1 x n+1 =

1

2 (y n + x n ) x n y n = y n 2 x n y n + x n

2

x n < y n y n+1 x n+1 <

1

2

(y n x n )

A(a, 0) B(0, b)

x + y

b

a

b

= 1 y = a (x a)

(0, 0)

y = a x a 2 + b 2 = k 2

b

b

y

y

b x a 2 + b 2 = k 2

= a (x a)

= a

a b x = a (xa) a 2 x = ax x =

b

b

2

a

1 + a 2

b

2

=

b 2 a

k

2

x = b 2 a ,

k

2

y = a 2 b

k

2

 

b 4 a 2 + a 4 b 2

k

4

x 2 + y 2 =

x 2 y 2 = a 6 b 6

k

8

=

a 2 b 2 (a 2 + b 2 )

k

4

=

a

2 b 2

k

2

(x 2 + y 2 ) 3 = k 2 x 2 y 2

r = a sin(2θ) (x 2 + y 2 ) 3 = 4a 2 x 2 y 2

M (x) = 0

0

1

0 0

1

x

0 x R

1

x, y R,

1

M(x) · M(y) = 0

0

x + y R

0

1

0

1

x

0 · 0

0

1

0

1

0

1

y

0 = 0

0

1

0

1

0

x + y

0

1

= M(x + y)

x, y, z R, M (x) · (M (y) · M (z)) = M (x) · M (y + z) = M (x + y + z) = M (x + y) · M (z) = (M (x) · M (y)) · M (z)

x, y R, M (x) · M (y) = M (x + y) = M (y + x) = M (y) · M (x)

x, m R, M (x) · M (m) = M (x)

0

0

1

1

M (x + m) = M (x) x + m = x m = 0 M (0) = 0

0

1

0

0

x, m R, M (x) · M (m) = M (0) x + m = 0 m = x M (x) M (x)

(A, ·)

 P (A) = 0,2 P (1 |A) = 0,8 P (2 |A) = 0,2 P (B) = 0,3 P (1 |B) = 0,5 P (2 |B) = 0,5 P (C) = 0,5 P (1 |C) = 0,6 P (2 |C) = 0,4

 P (2 ) = P (2 |A) · P (A) + P (2 |B) · P (B) + P (2 |C) · P(C) = 0,2 · 0,2 + 0,5 · 0,3 + 0,4 · 0,5 = 0,04 + 0,15 + 0,2 = 0,39

P(B|1 ) = P (1 |B) · P(B)

P

(1 )

=

P (1 |B)P(B)

=

1 P (2 )

0,5 · 0,3

1 0,39 =

0,15
0,2459016393
0,61 =

1 + x 2

D n =

x

0

0

x

0

0

0

0

0

 1 + x 2 x 0 ··· x 1 + x 2 x ··· 0 x 1 + x 2 0 0 0 0 0 0 ··· 0 0 0

 0 0 0 0 0 0 0 0 0 0 0 0 1 + x 2 0 x 0 x 1 + x 2 x x 1 + x 2

D

D

D

1

2

3

D n = (1 + x 2 )D n1 x

 x 0 0 x 1 + x 2 x 0 x 1 + x 2

···

= (1 + x 2 )D n1 x 2 D n2

= 1 + x 2 , = (1 + x 2 ) 2 x 2 = 1 + x 2 + x 4 , = (1 + x 2 )(1 + x 2 + x 4 ) x 2 (1 + x 2 ) = 1 + x 2 + x 4 + x 6

D k = 1 + x 2 + ··· + x 2k , k < n D n = (1 + x 2 )D n1 x 2 D n2 = (1 + x 2 )(1 + x 2 + ··· + x 2(n1) ) x 2 (1 + x 2 + ··· + x 2(n2) ) = 1 + x 2 + ··· + x 2n

n × n

1 + x 2 + ··· + x 2n

k, p, n N,

k

k

0 k p n

= p

k

n

p

n

p

1

1

n

n

k

0

n

p

n

p

+ n

1

+ ··· +

n n p

p

0

= 2 p

n

p

n

k

n

p

k = k

n!

·

(p k)!(n p)! = n!

✘✘

k! ·

(n k)!

(p k)!(n p)! · p!

1

(n k)!

k!

p! =

k!(p k)! · p!(n p)! = k p

p!

n!

n

p

n

0

n

p

+ n

1

n

p

1

1

+···+

n n p

p

0

= p

0

n

p

+ p

1

n

p

+

··· + p

p

n

p

2 p

n

p

=

n

p

p + p

0

1

p = + ··· + p

n

p

(1 + 1) p =